Emergence of methicillin-resistant Staphylococcus pseudintermedius in domestic animals - Carcamo-Tzic, Astrid (Kansas State University, 2022)
Staphylococcus pseudintermedius is a pathogenic bacterium of concern within the veterinary sector, and it is involved in numerous types of infections, including localized cutaneous infections, such as canine pyoderma, as well as systemic infections in the urinary, respiratory and reproductive systems. The emergence and high prevalence of methicillin resistant Staphylococcus pseudintermedius (MRSP) infections is becoming a growing concern in canine patients. Therefore, it is crucial to understand the involvement of S. pseudintermedius in canine disease pathology in order to gain a better understanding of its impact and provide insights into novel treatment strategies. A case study is reviewed in this report, which focuses on a MRSP-infected canine patient with pyoderma, and it discusses some of the common challenges in implementing effective treatments for this infection. Current and future treatment options against S. pseudintermedius are also discussed. Since this bacterium has caused a significant impact in the veterinary field, further research is needed to reduce the incidence and recurrence of MRSP infections in canine patients. This will be essential in order to understand how to improve control measures of this infection when there are a limited number of effective treatments.
Keywords: Staphylococcus pseudintermedius; Staphylococcus aureus; Methicillin resistance; Methicillin-resistant Staphylococcus pseudintermedius; Veterinary medicine; Antimicrobial resistance